Síntese, caracterização e estudo fotofísico de novos ligantes bipiridínicos aril substituídos - Bezerra, Lucas Fonseca (2019)
This work presents the results obtained for three novel bipyridine derivtives (mbpy-R), named as: 4'-methyl-4-(naphth-2-yl)-2,2'-bipyridine (mbpy-naph), 4'-methyl-4-(anthracen-2-yl)-2,2'-bipyridine (mbpy-anth), 4'-methyl-yl)-2,2'-bipyridine (mbpy-pyr). The compounds were synthesized from the condensation reactions of the precursor 4'-methyl-2,2'-bipyridine-4- carbaldehyde (mbpy-CHO) with the aromatic amines 2-naphthylamine (naph), 2- aminoanthracene (anth) and 1 -aminopyrene (pyr). Vibrational Spectroscopy in the Infrared Region and Nuclear Magnetic Resonance (NMR) data indicates that the aimed compounds were obtained with high purity. Thus, the work started an extensive description of the spectroscopic properties of theese compounds obtained by electronic absorption and emission spectroscopy in the ultraviolet and visible region. Also, additional data calculated using the Density Functional Theory (DFT) and Time Dependent Density Functional Theory (TD-DFT) were used to support the discussion. The UV-Vis absorption spectra shows that the energy bands are dependent of the attached group and the solvent indicating that an intramolecular charge transfer process occur within the molecule. As bigger is the substituent at the pyridines, more intense is the red shift observed for the absorption maximum, which is according to the frontier orbital energy levels energy gap calculated by TD-DFT: mbpy-naph (3.65 eV), mbpy-anth (3,.13 eV) e mbpy-pyr (3.01 eV). Emission quantum yield (Φ) values were calculated in ethanol using anthracene as reference. In comparison to the substituent aromatic, the mbpy-R compounds showed relatively low values of Φ: 0.001, 0.010 and 0.089 for R = naph, anth and pyr, respectively. Life-time values (τ) of the excited state were determined through emission decay curves in different solvents. The mpy-naph mbpy-anth and mbpy-pyr compounds presented monoexponential decay profiles with values of τ of 1.93, 13.55 and 4.15, respectively. Kinetic radioactive and non-radioactive constants for theese compounds suggests that its excited states decays preferencially by non-radioactive paths, that is accordance with the low singlet oxygen quantum yields determined for the series. The photophysical quenching of theese processes may occur predominant by vibrational deactivation, once the molecules has rotation axes which allows this type of energy loss.